1986
DOI: 10.1104/pp.82.2.473
|View full text |Cite
|
Sign up to set email alerts
|

NADH Nitrate Reductase and NAD(P)H Nitrate Reductase in Genetic Variants and Regenerating Callus of Maize

Abstract: ABSTRACI?Different organs of maize seedlings are known to contain different complements of NADH and NAD(P)H nitrate reductase (NR) activity.The study of the genetic programming that gives rise to such differences can be initiated by looking for genetic variants exhibiting different patterns of distribution of the above enzymes. We demonstrate in this work that scutella of very young maize seedlings contain NADH NR almost exclusively and that this activity is gradually replaced, as the seedling ages, with NAD(P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…as it was also suggested by many others earlier (George Sorger et al, 1986; Altaf Ahmed and Abdin, 1999) and the results of the present study are in accordance with the results reported earlier in mustard seedlings by Altaf and Abdin (1999), as it was explained that, whenever the nitrate concentration is more than 20mM, it is reduced to nitrite by NAD(P)H : NR as this isoform dominantly active than the other isoforms at nitrate concentrations above 20mM and can utilize either NAD(P)H alone or the combination of NADH : NAD(P)H as the coenzymes, whereas the other isoform can utilize NADH efficiently than NAD(P)H, optimally functions at low nitrate concentration (<10 mM). Hence, it could be concluded here that at 30 mM concentrations of nitrate and until day '15' to the day '20' the nitrate reduction was carried out by NAD (P) H: NR and thereafter with the decreased levels (low levels) of nitrate the isoform activity was gradually declined and NADH: NR was observed to be active at low levels of medium nitrogen.…”
Section: Nitrate Metabolismsupporting
confidence: 83%
“…as it was also suggested by many others earlier (George Sorger et al, 1986; Altaf Ahmed and Abdin, 1999) and the results of the present study are in accordance with the results reported earlier in mustard seedlings by Altaf and Abdin (1999), as it was explained that, whenever the nitrate concentration is more than 20mM, it is reduced to nitrite by NAD(P)H : NR as this isoform dominantly active than the other isoforms at nitrate concentrations above 20mM and can utilize either NAD(P)H alone or the combination of NADH : NAD(P)H as the coenzymes, whereas the other isoform can utilize NADH efficiently than NAD(P)H, optimally functions at low nitrate concentration (<10 mM). Hence, it could be concluded here that at 30 mM concentrations of nitrate and until day '15' to the day '20' the nitrate reduction was carried out by NAD (P) H: NR and thereafter with the decreased levels (low levels) of nitrate the isoform activity was gradually declined and NADH: NR was observed to be active at low levels of medium nitrogen.…”
Section: Nitrate Metabolismsupporting
confidence: 83%
“…Three apparently genetically different forms of NRs have been described for soybean leaves (Campbell and Smarelli 1986, Streit and Harper 1986, Sorger et al 1986. Vicia faba has been reported as only containing NADH-HR (Hewitt and Notton 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate reduction is a genetically controlled factor in the assim ilation of N (Table 4). Higher plants generally have more than one kind of nitrate reductase (Guerrero et al, 1981;Sorger et al, 1986). The enzyme may be constitutive or inducible by substrate (Heath-Pagliuso et al, 1984;Nelson et al, 1986;Streit et al, 1985).…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…Isozymes of nitrate reductase may be distributed in various plant organs and may change during plant development (Sorger et al, 1986). Nitrate reductase activity in plants and its distribution among various organs are under genetic control (Cove, 1979;Fortini et al, 1975;Gallagher et al, 1980;Rao et al, 1977;Sorger et al, 1986;Warner et al, 1969).…”
Section: Nitrate Reductionmentioning
confidence: 99%
See 1 more Smart Citation